Gait analysis: a cost and time efficient video method for use in the clinic or classroom. - Macfarlane PA; Nielsen DH (Clinical Kinesiology: Journal of the American Kinesiotherapy Association)
The purpose of this paper is to describe a system of gait analysis that is user-friendly and time- and cost-efficient. The system is designed to analyze normal and pathological walking and running gait from a sagittal view with reference to foot placements and can be used in a clinical or nonrestricted setting. The equipment needed is a VHS video camera, a monitor, and a VCR with a jog shuttle control, and access to a time code generator. Temporal, distance, and symmetry variables are calculated using data derived from the video recording of at least three gait cycles. A manual and IBM-compatible program disks for data analysis are available for $20 from the author. Within 10 minutes a walking or running trial can be recorded and analyzed, with data printed and stored on a disk.